2009
DOI: 10.1093/brain/awp034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of evoked potentials to dyadic tones after cochlear implantation

Abstract: Auditory evoked potentials are tools widely used to assess auditory cortex functions in clinical context. However, in cochlear implant users, electrophysiological measures are challenging due to implant-created artefacts in the EEG. Here, we used independent component analysis to reduce cochlear implant-related artefacts in event-related EEGs of cochlear implant users (n = 12), which allowed detailed spatio-temporal evaluation of auditory evoked potentials by means of dipole source analysis. The present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
82
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 64 publications
(99 citation statements)
references
References 67 publications
15
82
2
Order By: Relevance
“…This confirms previous research which reported differences in the sensory processing of auditory stimuli in CI users and NH listeners [Finke et al, 2015;Finke et al, 2016;Oates et al, 2002;Sandmann et al, 2009Sandmann et al, , 2010Sandmann et al, , 2015.…”
Section: Behavioral Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This confirms previous research which reported differences in the sensory processing of auditory stimuli in CI users and NH listeners [Finke et al, 2015;Finke et al, 2016;Oates et al, 2002;Sandmann et al, 2009Sandmann et al, , 2010Sandmann et al, , 2015.…”
Section: Behavioral Resultssupporting
confidence: 91%
“…Independent components reflecting eye blinks, horizontal eye movements, and CI artifacts were removed [Jung et al, 2000a, b]. Components representing CI artifacts were identified by the centroid on the side of the implanted device and by the time course of component activity, which typically showed a sharp onset around 30 ms after stimulus onset (for details about the reduction of CI artifacts by means of independent component analysis, see Debener et al [2008], Sandmann et al [2009], and Viola et al [2011]). Then, missing channels located in proximity to the speech processor and transmitter coil were interpolated using spherical spline interpolation (mean number of missing electrodes: 6.3; SD: 2.11; range: 3-10 [Perrin et al, 1989]).…”
Section: Data Recording and Analysismentioning
confidence: 99%
“…Independent components reflecting eye-blinks, horizontal eye movements, electrical heartbeat activity and CI artifacts were removed (Jung et al, 2000a(Jung et al, , 2000b. Components representing CI artifacts were identified by the centroid on the side of the implanted device and by the time course of component activity (for details about the reduction of CI artifacts by means of ICA see (Debener et al, 2008;Sandmann et al, 2009;Viola et al, 2011)). After removal of artifact-related ICA components, channels which were missing due to the speech processor and transmitter coil were interpolated.…”
Section: Electrophysiological Data: Recording and Data Processingmentioning
confidence: 99%
“…Among the long-latency ERPs, the N1-P2 complex seems to be particularly useful to study auditory processing because it can be evoked by a variety of stimuli. Alterations in long-latency ERPs have been reported for subject populations who experience perception difficulties, among them individuals with hearing impairment and CI users (Oates et al, 2002;Sandmann et al, 2009). Moreover, the N1-P2 complex is modulated by background noise.…”
Section: Introductionmentioning
confidence: 99%
“…As it is evoked by the onset of a pitch and its morphology is different from an N100 response, this IRN onset response was labeled as pitch onset response (POR) [Krumbholz et al, 2003]. In contrast to magnetoencephalographic recordings, auditory-evoked potentials have been recorded by EEGs in CI users [Kraus et al, 1993;Debener et al, 2007;Sandmann et al, 2009;Rahne et al, 2014]. Equivalent to the POR, the acoustic change complex was evoked by a slight change to the fundamental frequency of a vowel stimulus and measured successfully in 1 CI user by Martin [2007].…”
mentioning
confidence: 99%